KOLEKSI REFERENSI NYAMUK Anopheles DI BEBERAPA KABUPATEN DENGAN MASALAH MALARIA DI PULAU JAWA - Nur Ika Hariastuti (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2011)
Malaria has continued to be the health problem in Central Java, East Java and Special Region Yogyakarta (DIY) provinces. Various efforts of prevention and control have been carried out, but the results were still not promising. One of the causes is the lack of understanding about the species and various aspects of vector bionomics. Reference collection were conducted to identify the Anopheles species in the district where malaria was endemic (Central Java, East Java and DIY Province). Samples were collected with purposive sampling method. The results indicated that in Central Java Province there were 8 Anopheles species; An. indefinitus. An. barbirostris, An. vagus, An. subpictus in Cilacap District, An. aconitus, An. maculatus, An. kochi, An. barbirostris, An. vagus, An. annularis in Pemalang District. An. maculatus, An.barbirostris, An. vagus in Kendal District. In East Java there was six Anopheles species; An. aconitus, An. maculatus, An.barbirostris, An. kochi in Trenggalek District, An. aconitus, An. maculatus, An. barbirostris, An. vagus, An. annularis in Pacitan District. In DIY, Sleman District there was six Anopheles species; An. aconitus, An. barbirostris, An. vagus in Mlati SubDistrict and An. aconitus, An. maculatus, An. balabacensis, An. barbirostris, An. vagus, An. annularis in Turi SubDistrict.